Interventional Traps in Ectatic Coronary Arteries: A Case Report - Krešimir Gabaldo; Marijana Knežević Praveček; Domagoj Vučić; Domagoj Mišković; Ivan Bitunjac; Ivica Dunđer; Božo Vujeva; Blaženka Miškić; Katica Cvitkušić Lukenda (Acta Clinica Croatica, 2024)
Coronary artery ectasia or aneurysms are dilatation of an arterial segment to a diameter at least 1.5 times that of the adjacent normal. Blood flow through such arteries is disturbed and turbulent, which, with the activation of endothelium, leads to chronic thrombosis in the blood vessel wall. Percutaneous coronary interventions in ectatic / aneurysmal vessels carry a high risk of complications, primarily a “no-reflow” phenomenon. No-reflow is common in patients with acute coronary syndrome, especially ST elevation myocardial infarction (STEMI). In this article, we present the occurrence of the no-reflow phenomenon in a stable patient undergoing percutaneous intervention due to a significant stenosis of the aneurysmally altered right coronary artery. Despite the rapid placement and optimization of stents and the applied drug therapy combined with thromboaspiration periprocedurally, it was not possible to establish TIMI 3 flow. However, after the initial failure and development of periprocedural STEMI, the patient was successfully stabilized with unexpectedly good recovery of infarcted myocardial function. Control coronarography 6 weeks after the initial event confirmed a proper stent patency with normal TIMI 3 flow.